Unknown Records of Dovzhenko's Diaries - Zilynskyj, Bohdan (Iluminace, 1990)
Review of the edition of Dovzhenko's diaries from the war years.
Keywords: Oleksandr Dovzhenko; diaries of a filmmaker; Ukrainian film; Soviet film during World War II